Uptake of OER by Staff in Distance Education in South Africa - de Hart, Kerry Lynn; Chetty, Yuraisha B; Archer, Elizabeth (International Review of Research in Open and Distributed Learning, 2015)
Open Educational Resources (OER) emerged within the context of open education which is typically characterized by the sharing of knowledge and resources and the exchange of ideas. Unisa as a mega open distance learning (ODL) university has publicly communicated its intention to take part in the use and creation of OER. As global and local university research on OER is limited, this prompted an investigation to gauge the uptake of OER at Unisa, by staff, with the purpose of institutional information gathering for decision making and planning in this area. During 2014, a survey was undertaken for this reason. The survey examined knowledge of OER, Intellectual Property (IP) Rights and Licensing, participation in OER, barriers to OER and OER in the Unisa context with a view to determining the stage at which the institution is in terms of adopting and engaging with the OER initiative. The results indicated that although there is knowledge and understanding of OER, this has not been converted into active participation. It further highlighted the barriers that are prohibiting the operationalization of OER and resulted in recommendations for planning and activities in respect of OER. The constructs investigated and the results thereof might not be generalizable to other contexts, although commonalities are likely. The insights should prove useful to a variety of contexts. The paper illustrates the need for institutions, irrespective of context, to take stock of the impact of initiatives and in this case evaluate how the institution and staff mature through various phases in the uptake of OER in order to guide effective planning, decision making and implementation.